Influence of Joint Angle on Residual Force Enhancement in Human Plantar Flexors - Fukutani, Atsuki; Misaki, Jun; Isaka, Tadao (Frontiers in Physiology, 2017)
Compared to pure isometric contractions, isometric muscle force at a given length is larger when the eccentric contraction is conducted before the isometric contraction. This phenomenon is widely known as residual force enhancement, and has been confirmed consistently in isolated muscle experiments. The purpose of this study was to confirm whether residual force enhancement also occurs in human plantar flexors and to examine its joint angle dependence. Eleven men participated in this study. Isometric joint torque was measured in a Control trial (pure isometric contraction) and Residual force enhancement (RFE) trial (isometric contraction after eccentric contraction) at plantar flexion 0° (Short condition) and dorsiflexion 15° (Long condition). Fascicle length and pennation angle of the medial gastrocnemius were measured simultaneously to evaluate the influence of architectural parameters on isometric joint torque. Isometric joint torque observed in the Short condition was not significantly different between the Control and RFE trials (Control: 42.9 ± 8.0 Nm, RFE: 45.1 ± 8.4 Nm) (p = 0.200). In contrast, significant differences in isometric joint torque were observed in the Long condition between Control and RFE trials (Control: 40.5 ± 9.3 Nm, RFE: 47.1 ± 10.5 Nm) (p = 0.001). Fascicle length and pennation angle were not different between Control and RFE trials in the Short and Long conditions. Isometric joint torque was larger when eccentric contraction was conducted before isometric contraction while architectural differences were not observed, indicating that residual force enhancement occurs in human plantar flexors. However, the influence of residual force enhancement may be limited in dorsiflexed positions because the magnitude of residual force enhancement is considered to be prominent in the descending limb (long muscle length condition) and small in the ascending limb (short muscle length condition) where human plantar flexors operate in plantar flexed positions.